Sowing wildflower meadows in Mediterranean peri-urban green areas to promote grassland diversity - Fernandes, Mariana P.; Matono, Paula; Almeida, Erika; Pinto-Cruz, Carla; Belo, Anabela D. F. (Frontiers in Ecology and Evolution, 2023)
The increase of urban areas and their infrastructure network is homogenizing the landscape and threatening biodiversity and ecosystems functions and services. Wildflower meadows have a high biodiversity value and can prosper in degraded areas dominated by nitrophilous species, making them suitable to be used in peri-urban and urban areas to promote local flora, create habitat for pollinators and other small fauna, and increase overall biodiversity. Moreover, the application of wildflowers seed mixes suitable for rehabilitating anthropized environments should be restricted to native species of regional origin, and the results properly monitored. However, thorough monitoring of seed mixes evolution is uncommon. This study evaluates the effectiveness of a seed mix of wild native species developed to promote grassland diversity in Mediterranean peri-urban areas. The study was divided into two sequential phases. Firstly, a preparatory phase consisted in developing two seed mixes and sowing them (autumn 2016) in ex-situ plots (three plots of 5x2 m2 per mix) at an experimental field to choose the one with the best performance. The second phase consisted of the in-situ application (autumn 2018) of the chosen seed mix by sowing 14 plots (10x2 m2) in pocket parks distributed along pedestrian trails of South Portugal. All plots were monitored through floristic surveys for two springs (ex-situ trials: 2017 and 2018; in-situ trials: 2019 and 2020). All sowed species germinated in the in-situ plots over the first two years. The seed mix application positively contributed to the floristic community, generating a significant increase in the total species richness, diversity, evenness, and vegetation cover. The seed mix establishment did not require watering nor soil fertilizing and the mowing frequency was low (once in late spring), contributing to sustainable and low-cost management of these green areas. The tested seed mix promoted native flora diversity rapidly and seems suitable for use in peri-urban context under identical climate conditions. Given the small number of native seed mixes tested in the Mediterranean, this study represents a contribution toward improved management standards of native flora diversity in Mediterranean green urban and peri-urban areas.